745 views
1 vote
(W^8/w^8)^-6 simplify

(W^8/w^8)^-6 simplify-example-1

1 Answer

2 votes

Answer:


(1)/(w^(36))

Explanation:

Given:


((w^8)/(w^2))^(-6)

We need to Simplify the equation;

To Simplify the equation we will use Law of indices.


(x^a)/(x^b)=x^(a-b)


(w^8)/(w^2) = w^(8-2)= w^6

Now we get;


(w^6)^(-6)

Now Simplifying equation we will use Law of indices we get;


(x^a)^b=x^(a* b)


(w^6)^(-6) =w^(6* -6) = w^(-36)

Also again Law of Indices states;


x^(-a)= (1)/(x^a)


w^(-36)= (1)/(w^(36))

Hence the Final Answer is
(1)/(w^(36))

User Ofisora
by
5.9k points